IDENTIFIKASI POTENSI DAYA TARIK EKOWISATA AIR TERJUN BUKIT TILUNG (NANGA ARONG KABUPATEN KAPUAS HULU) - Natalis, Marinus R; Erianto, Erianto; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2020)
This research aimed to describe the Identification of the Potential Attractiveness of Bukit Tilung Waterfall Ecotourism. This study used an in-depth interview approach to selected respondents using the Survey Method and was carried out at Bukit Tilung Waterfall in Nanga Arong Hamlet, Kalis District, Kapuas Hulu Regency. Data collection methods used were; Direct Observation, Interview, Literature, and Documentation. Based on the results of the research, Bukit Tilung Waterfall had the potential for an excellent ecotourism attraction to be developed as a natural tourist destination. The condition of the area had a uniqueness, sensitivity of natural resources, had a choice or variety of natural tourism activities, cleanliness of the location air, comfort, and security are guaranteed. Bukit Tilung Waterfall had several potentials namely; (1) Flora Biological Potential such as; Moss Plants in Rocks, Trees, and Semar Bags (Nepenthes), (2) Potential of Biological Fauna such as; Shrimp (Caridea), Fish and Primates, (3) Non-biological Potentials such as; Bukit Tilung Waterfall, Pond or lubuk, Natural Beauty, and Culture. (4). Recreational Activity Options such as; Fishing Activities, Tracking (Travel), and Educational Activities.Keywords: Bukit Tilung, Ecotourism, Waterfall